THE PRACTICE OF PUBLIC INITIAL PUBLIC OFFERING OF SHARES BY A JOINT-STOCK COMPANY - Ismailov Musabek (Scholars Digest Publishing, 2023)
Due to the growing demand for investment in foreign countries, many companies are using various ways to attract them. In particular, the method of increasing the company's capital by placing its shares in the primary market on the basis of IPOs. Through this method, the company offers the fairest assessment of the market value of its assets. Listed companies will be required to meet high standards of financial and business disclosure, as well as create investment appeal for potential investors.
Keywords: secondary public offering, financial market, liquidity, volatility initial public offering.